2019
DOI: 10.3390/ph12040166
|View full text |Cite
|
Sign up to set email alerts
|

New 55Co-labeled Albumin-Binding Folate Derivatives as Potential PET Agents for Folate Receptor Imaging

Abstract: Overexpression of folate receptors (FRs) on different tumor types (e.g., ovarian, lung) make FRs attractive in vivo targets for directed diagnostic/therapeutic agents. Currently, no diagnostic agent suitable for positron emission tomography (PET) has been adopted for clinical FR imaging. In this work, two 55Co-labeled albumin-binding folate derivatives-[55Co]Co-cm10 and [55Co]Co-rf42-with characteristics suitable for PET imaging have been developed and evaluated. High radiochemical yields (≥95%) and in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 32 publications
4
57
0
Order By: Relevance
“…In contrast, the 55 Co-labeled folate conjugate (14, Figure 4) exhibited lower liver uptake compared to the 64 Cu-labeled radiolabeled folates. This observation was explained by the fact that 55 Co in contrast to 64 Cu does not accumulate in the liver when it is released by the DOTA or NODAGA chelator since it behaves as a calcium mimetic [49].…”
Section: α-And γ-Derivatization Of the Glutamate Groups In Folic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the 55 Co-labeled folate conjugate (14, Figure 4) exhibited lower liver uptake compared to the 64 Cu-labeled radiolabeled folates. This observation was explained by the fact that 55 Co in contrast to 64 Cu does not accumulate in the liver when it is released by the DOTA or NODAGA chelator since it behaves as a calcium mimetic [49].…”
Section: α-And γ-Derivatization Of the Glutamate Groups In Folic Acidmentioning
confidence: 99%
“…In vitro cell binding studies showed specificity of the folate derivative to FR, however, no results of in vivo studies with FR-positive tumor-bearing mice have been reported. In 2019, Radford et al [ 49 ] reported the radiolabeling of folate conjugates rf42 and cm10 with 55 Co for PET imaging representing the first cobalt-55-labeled radiolabeled folates ever to be reported in the literature. A high radiochemical yield of ≥95% and in vitro stability of ≥93% of both tracers were obtained.…”
Section: Structure-activity-relationship and Library Design Of Radmentioning
confidence: 99%
“…The beta isoform of the folate receptor (FR-β), distinctly expressed on activated macrophages, has been recognized as a promising imaging marker for inflammatory conditions such as rheumatoid arthritis 2 7,8 , with the latter two already reaching initial clinical phase 9,10 . Other recently developed FR-targeted tracers include reduced 18 F-folate conjugates 11 , 55 Co-labeled albumin-binding folate derivatives 12 and [ 68 Ga]NOTA-folate 13 , which have been investigated for imaging FR-overexpressing tumors in preclinical studies. In a previous study, we showed that 18 F-FOL PET successfully visualized FR-β-positive macrophages in mouse and rabbit models of atherosclerosis 3 .…”
Section: Table Of Content/abstract Graphic Introductionmentioning
confidence: 99%
“…In the ongoing clinical trial the first 68 Ga-folate PET radiotracer ([ 68 Ga]Ga-EC2115) is tested to evaluate the possibility of differentiating COPD (chronic obstructive pulmonary disease) patients from control subjects and determine whether PET signal correlates with measurements of inflammation, disease severity, and rate of disease progression [16]. Currently, data on several folic acid based radiopharmaceuticals with PET-radionuclides, such as 18 F, 68/66 Ga, 152 Tb, 64 Cu, 55 Co and 44 Sc have been presented and even more new conjugates are under development [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%